ERS International Congress, Madrid, 2019: highlights from the Respiratory Intensive Care Assembly. Issue 1 (9th March 2020) - Satici, Celal; López-Padilla, Daniel; Schreiber, Annia; Kharat, Aileen; Swingwood, Ema; Pisani, Luigi; Patout, Maxime; Bos, Lieuwe D.; Scala, Raffaele; Schultz, Marcus J.; Heunks, Leo
The Respiratory Intensive Care Assembly of the European Respiratory Society is delighted to present the highlights from the 2019 International Congress in Madrid, Spain. We have selected four sessions that discussed recent advances in a wide range of topics: from acute respiratory failure to cough augmentation in neuromuscular disorders and from extra-corporeal life support to difficult ventilator weaning. The subjects are summarised by early career members in close collaboration with the Assembly leadership. We aim to give the reader an update on the most important developments discussed at the conference. Each session is further summarised into a short list of take-home messages. The #ERSCongress in Madrid had some great sessions on respiratory intensive care. This article highlights the most important sessions. http://bit.ly/2GtT0qL